2016
DOI: 10.1097/aap.0000000000000295
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Regional Anesthesia and Patient Safety

Abstract: Since the original 2010 publication of this analysis, evidence has continued to support the concept that ultrasound (US) guidance does not meaningfully affect the incidence of peripheral nerve injury (PNI) associated with regional anesthesia. Similar confirmatory evidence attests to US guidance reducing the incidence and intensity of hemidiaphragmatic paresis (HDP) but not eliminating it. Literature published since late 2009 reports the effective role of US guidance in reducing the incidence of local anestheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
2
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 230 publications
(118 citation statements)
references
References 110 publications
2
106
2
8
Order By: Relevance
“…Ultrasound guidance reduces the likelihood of any LAST event, yet seizure and/or cardiac arrest still occur at an estimated rate of 0.26/1000 ultrasound-guided blocks. 43 …”
Section: Registriesmentioning
confidence: 99%
“…Ultrasound guidance reduces the likelihood of any LAST event, yet seizure and/or cardiac arrest still occur at an estimated rate of 0.26/1000 ultrasound-guided blocks. 43 …”
Section: Registriesmentioning
confidence: 99%
“…In turn, this could (theoretically) decrease the incidence of PONS 276. However, quality assurance and registry studies have found no difference in the prevalence of PONS between US and other localization techniques 270 276 291.…”
Section: Complications Of Lower Extremity Nerve Blocksmentioning
confidence: 99%
“…5,6 The incidence of seizures due to intravenous local anaesthetic injection varies between 1 per 800 and 1 per 1500 when nerve stimulation is used. 7,8 Peripheral neurological complications not involving haematoma or infection are rare, 9 with the incidence of permanent nerve injury being approximately 2 per 10 000 axillary brachial plexus blocks performed with nerve stimulation, reported in the last survey of the SOS French Regional Anaesthesia Hotline. 10 blocks, the number of patients required to compare ultrasound guidance with nerve stimulation is prohibitively large.…”
Section: Introductionmentioning
confidence: 99%